2014
DOI: 10.1097/mpg.0000000000000400
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Stiffness Measurement by Transient Elastography to Diagnose Portal Hypertension in Children

Abstract: SSM by TE is feasible in children and the results reflect the degree and occurrence of complications. A prospective follow-up study with larger patient numbers and performance of screening endoscopies appears justified and desirable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 28 publications
1
48
0
Order By: Relevance
“…Some studies have suggested that spleen stiffness may be a marker of portal hypertension [80, 81]. Additionally, spleen stiffness may help predict the presence of esophageal varices and the risk of bleeding [82].…”
Section: Future Directionsmentioning
confidence: 99%
“…Some studies have suggested that spleen stiffness may be a marker of portal hypertension [80, 81]. Additionally, spleen stiffness may help predict the presence of esophageal varices and the risk of bleeding [82].…”
Section: Future Directionsmentioning
confidence: 99%
“…Liver transient elastography (L‐TE) and liver ARFI (L‐ARFI) estimate liver stiffness, which correlates with fibrosis . Some studies have investigated spleen stiffness, and most of them have focused on the correlation with oesophageal varices and portal hypertension . Elevated spleen stiffness obtained by ARFI (S‐ARFI) was significantly associated with increased hepatic vein pressure gradient diagnosing portal hypertension in a recent study …”
Section: Introductionmentioning
confidence: 99%
“…Sonoelastography of the liver and spleen has been studied as an alternative modality for predicting portal hypertension and esophageal varices . Previous studies using transient elastography have suggested that spleen stiffness has high diagnostic accuracy in predicting portal hypertension and esophageal varices because spleen stiffness reflects splanchnic flow better than liver stiffness …”
mentioning
confidence: 99%